Visualizing metabolites at the cellular level: advancements in 3-micron laser desorption mass spectrometry imaging - Murray,RT; Battle,RA; Simon,D; Xiang,Y; Robinson,K; Azevedo,Magalhães SF; Wang,Y; Runcorn,TH; Takats,Z (SPIE, 2024)
By combining high beam quality picosecond pulsed optical parametric amplifiers at 2.94 μm with Rapid Evap-ortive Ionisation Mass Spectrometry (REIMS), we have demonstrated record spatial pixel resolutions for ambientmass spectrometry (MS) imaging of < 10 μm. In this contribution, we introduce our work in this area, demon-strating the platform workflow and highlighting recent results of metabolic imaging at the single cell resolutionlevel.